Asksia AI LOGO

Sia

Question
Math
Posted 9 months ago
Heba was asked to find this integral using uu-substitution:
(12x1)6x2x+1dx
\int(-12 x-1) \sqrt{-6 x^{2}-x+1} d x


How should Heba define uu ?

Choose 1 answer:
(A) u=6x2x+1u=-6 x^{2}-x+1
(B) u=6x2x+1u=\sqrt{-6 x^{2}-x+1}
(c) u=12x1u=-12 x-1
(D) u=xu=\sqrt{x}
Sign in to unlock the answer
Answer from Sia
Posted 9 months ago
Solution by Steps
step 2
We identify the function under the square root, 6x2x+1-6x^2 - x + 1, as a potential uu because its derivative, 12x1-12x - 1, is present outside the square root
step 3
Define uu as the function under the square root: u=6x2x+1u = -6x^2 - x + 1
step 4
Differentiate uu with respect to xx to find dudu: du=(12x1)dxdu = (-12x - 1)dx. This shows that our choice of uu is correct because (12x1)dx(-12x - 1)dx is present in the integral
step 5
Substitute uu and dudu into the integral and solve. The integral becomes udu\int \sqrt{u} \, du, which is straightforward to integrate
A
Key Concept
uu-substitution
Explanation
In uu-substitution, we choose uu to be a function inside the integral that simplifies the integral when we substitute dudu for the corresponding terms in dxdx.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question